2018
DOI: 10.1002/cncy.22035
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy in pancreatic cysts with cytology of high‐grade epithelial atypia

Abstract: Background The risk of malignancy is weighed against the attendant risks of surgery in the clinical management of pancreatic cysts. The latter are a group of histologically diverse and prognostically variable entities, and the risk of malignancy therein is primarily based on imaging characteristics—with or without high‐grade atypia. Cytologic criteria for high‐grade atypia in intraductal papillary mucinous neoplasms have recently been defined, and its recognition in all pancreatic cysts may help to guide manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The concerning features for malignancy of IPMN, according to the 2012 Fukuoka Consensus Guidelines, are obstructive jaundice in a patient with a cystic lesion of the head of the pancreas, an enhancing solid component within the cyst, and a dilated main pancreatic duct equal or greater than 10 mm. Cysts greater than 30 mm, thickened/enhancing cyst walls, main duct size of 5 to 9 mm, non‐enhancing mural nodule, and abrupt change in the calibre of the pancreatic duct with distal pancreatic atrophy/regional lymphadenopathy, are considered as worrisome features for malignancy 17,27 …”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…The concerning features for malignancy of IPMN, according to the 2012 Fukuoka Consensus Guidelines, are obstructive jaundice in a patient with a cystic lesion of the head of the pancreas, an enhancing solid component within the cyst, and a dilated main pancreatic duct equal or greater than 10 mm. Cysts greater than 30 mm, thickened/enhancing cyst walls, main duct size of 5 to 9 mm, non‐enhancing mural nodule, and abrupt change in the calibre of the pancreatic duct with distal pancreatic atrophy/regional lymphadenopathy, are considered as worrisome features for malignancy 17,27 …”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…In one study looking at the overall agreement between cytopathologists when applying a two‐tiered approach to grading mucinous cyst atypia (low or high‐grade), a poor performance was noted particularly in histologically confirmed low‐grade cysts, with many of the cytopathologists over‐interpreting the grade of atypia . In contrast, however, most studies have shown that the cytological grade of a mucinous cyst correlates well with histology, with high‐grade atypia being the only statistically significant predictor of malignancy . Grading the atypia of the cyst lining cells is of utmost importance, since low‐grade lesions are usually managed conservatively, and high‐grade lesions require prompt surgical intervention.…”
Section: Experience With the Use Of The Pb System Worldwidementioning
confidence: 99%
“…18 In contrast, however, most studies have shown that the cytological grade of a mucinous cyst correlates well with histology, with high-grade atypia being the only statistically significant predictor of malignancy. 12,17,19 Grading the atypia of the cyst lining cells is of utmost importance, since low-grade lesions are usually managed conservatively, and high-grade lesions require prompt surgical intervention. Recent prospective studies on the use of the PB System have showed a striking difference in ROM between cysts with low vs high-grade atypia, with an absolute ROM close to 90% for cysts with high-grade atypia, which clearly justifies a distinct therapeutic approach for these lesions based on the cytological grade.…”
Section: Experience With the Use Of The Pb System Worldwidementioning
confidence: 99%
“…6,7 Thus, cytological diagnosis using pancreatic EUS-FNA provides important information on the indications for surgery. 5,8,9 The Japanese Pancreas Society recommends EUS-FNA as the rst choice for pathological diagnosis of pancreatic cancer. 10 Although most pathological diagnoses using EUS-FNA samples are straightforward, some inconclusive pathological ndings were reported, especially in small and/or degraded samples, and when differentiating atypical epithelium and well-differentiated cancer with weak cytological atypia, as well as pancreatic mucinous neoplasms from the contaminants of gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous studies reported that atypical cytological ndings by pancreatic EUS-FNA highly indicated pancreatic neoplasms (55%) including cancer (36%). 4 Cytological diagnosis was also highly speci c for detection of pancreatic cystic tumors such as intraductal papillary mucinous neoplasm 5 and mucinous cyst neoplasm. 6,7 Thus, cytological diagnosis using pancreatic EUS-FNA provides important information on the indications for surgery.…”
Section: Introductionmentioning
confidence: 99%